Three new species of Neuraphes in eastern Qinghai-Tibet Plateau (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Three new ant-like stone beetle species: Neuraphes (Pararaphes) sichuanus sp. n., N. (P.) tuyuhun sp. n., and N. (P.) miniqinghaiensis sp. n. are described from Sichuan and Qinghai provinces of China. Another species, close to N. qinghaiensis Jałoszyński, is illustrated, but not formally described because of unclear diagnostic characters. The placement of Neuraphes species that inhabit mountain ranges surrounding Qinghai-Tibet Plateau in the subgenus Pararaphes is discussed and their distribution is summarized.